The efficacy of molecular markers analysis with integration of sensory methods in detection of aroma in rice - Yeap, H.Y.; Faruq, G.; Zakaria, H.P.; Harikrishna, J.A. (Hindawi Publishing Corporation, 2013)
Allele Specific Amplification with four primers (External Antisense Primer, External Sense Primer, Internal Nonfragrant Sense Primer, and Internal Fragrant Antisense Primer) and sensory evaluation with leaves and grains were executed to identify aromatic rice genotypes and their F1 individuals derived from different crosses of 2 Malaysian varieties with 4 popular land races and 3 advance lines. Homozygous aromatic (fgr/fgr) F1 individuals demonstrated better aroma scores compared to both heterozygous nonaromatic (FGR/fgr) and homozygous nonaromatic (FGR/FGR) individuals, while, some F1 individuals expressed aroma in both leaf and grain aromatic tests without possessing the fgr allele. Genotypic analysis of F1 individuals for the fgr gene represented homozygous aromatic, heterozygous nonaromatic and homozygous nonaromatic genotypes in the ratio 20 : 19 : 3. Genotypic and phenotypic analysis revealed that aroma in F1 individuals was successfully inherited from the parents, but either molecular analysis or sensory evaluation alone could not determine aromatic condition completely. The integration of molecular analysis with sensory methods was observed as rapid and reliable for the screening of aromatic genotypes because molecular analysis could distinguish aromatic homozygous, nonaromatic homozygous and nonaromatic heterozygous individuals, whilst the sensory method facilitated the evaluation of aroma emitted from leaf and grain during flowering to maturity stages.